Development of Polymethylmethacrylate Based Composite for Gas Sensing Application. (2011) - Devikala, S.; Kamaraj, P.
Abstract : Gas detection instruments are increasingly needed for industrial health and safety, environmental monitoring and process control. Conductive polymer composites have various industrial applications. The composite prepared by mixing carbon black with polymethylmethacrylate (PMMA) has very good gas sensing applications. The gas sensors based on carbon nanotube/polymer, ceramic and metal oxide composites such as epoxy, polyimide, PMMA / Barium titanate and tin oxide have also been developed. In the present work, a new composite has been prepared by using PMMA and ammonium dihydrogen phosphate (ADP). The PMMA/Ammonium dihydrogen phosphate (PMADP) composites PMADP 1 and PMADP 2 were characterized by using Powder XRD. The thick films of the composite on glass plates were prepared by using a spin coating unit at 9000 rpm. The application of the thick film as gas sensor has been studied between 0 and 2000 seconds. The results reveal that the thick film of PMADP composite can function as a very good gas sensor.